Ishemic Stroke (Texas Journal of Medical Science, 2025)
Ischemic stroke is an acute neurological syndrome caused by the sudden interruption of cerebral blood flow due to thrombus formation or atherosclerotic occlusion of intracranial vessels. This article reviews the pathogenesis, key clinical manifestations, diagnostic modalities, and stepwise treatment protocols for ischemic stroke. Timely recognition and appropriate management significantly reduce mortality and long‐ term disability.